2019
DOI: 10.1016/j.bmc.2019.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of atorvastatin via asialoglycoprotein receptor (ASGPR)

Abstract: Targeted drug delivery platforms can increase the concentration of drugs in specific cell populations, reduce adverse effects, and hence improve the therapeutic effect of drugs. Herein, we designed two conjugates by installing the targeting ligand GalNAc (N-acetylgalactosamine) onto atorvastatin (AT). Compared to the parent drug, these two conjugates, termed G2-AT and G2-K-AT, showed increased hepatic cellular uptake. Moreover, both conjugates were able to release atorvastatin, and consequently showed dramatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Previous studies reported that atorvastatin esters were not able to cause a biological effect until free atorvastatin was released. 13,21 Nevertheless, in our case esters 1b and 2a demonstrated slight inhibition of the HMG-CoA reductase (Fig. 2).…”
Section: Resultsmentioning
confidence: 41%
See 3 more Smart Citations
“…Previous studies reported that atorvastatin esters were not able to cause a biological effect until free atorvastatin was released. 13,21 Nevertheless, in our case esters 1b and 2a demonstrated slight inhibition of the HMG-CoA reductase (Fig. 2).…”
Section: Resultsmentioning
confidence: 41%
“…Atorvastatin conjugates underwent a two-step hydrolysis process that includes lactone formation as was demonstrated by the previous report. 13 Therefore, the linearity of the atorvastatin release corresponds to the pseudo zero-order intramolecular deesterification.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sialic acid glycoprotein receptor (ASGPR) is a promising drug target for the HCC treatment because of its high expression on the surface of HCC cell line (Poelstra et al., 2012 ; Nair et al., 2019 ; Zhang et al., 2019 ). Also, lactoferrin (LF) and ASGPR can bind in a non-dependent way with high affinity.…”
Section: Introductionmentioning
confidence: 99%